AN ANALYSIS OF SPEECH ACTS IN THE CROODS MOVIE - Ajeng Fala Intan Kumala (Postgraduate School, Universitas Nusa Cendana, 2018)
This research is aimed to identify the locutionary, illocutionary and perlocutionary acts in the The Croods movie and to analyze the meaning of locutionary, illocutionary and perlocutionary acts in the The Croods movie. The method used in collecting the data is qualitative. This study was conducted by collecting any relevant data and information about the topic or problem of the study from books and internet that are available for the analysis. This research used some steps to be collected: watching the movie, making the transcription and identifying the dialogue, after that classifying the actor’s utterances, and finally classifying the meaning of locutionary acts, illocutionary acts, and perlocutionary acts. The result shows that all types of speech act occur in the The Croods movie. In this study, the locutionary act is the actor’s utterances. The illocutionary act that mostly used in The Croods Movie are asking and commanding. The perlocutionary act is often used non-literally perlocutionary act